Communicating Cross-Border Protection for Non-Procedural Indonesian Migrant Workers in Malaysia - Peny, Stellania; Sutantri, Sintia Catur; Hakim, Arif Rahman; Wiryawan, Widiandaru (Feedback International Journal of Communication, 2025)
Non-procedural labor migration remains a persistent governance challenge in Southeast Asia, particularly along the Indonesia–Malaysia corridor. While regulatory and enforcement approaches have been widely studied, the role of policy communication in shaping migrant behavior and protection outcomes remains underexplored. This study examines how BP2MI’s policy communication functions as a determinant of migration governance through prevention, cross-border coordination, and discourse. This study employs a qualitative case study approach, combining in-depth interviews, document analysis, and institutional data from BP2MI and related agencies. The analysis focuses on preventive communication practices, cross-border institutional coordination in the Recalibration Program, and discursive gaps between policy narratives and migrant experiences. Descriptive statistical data on migrant placement and prevented non-procedural departures are used to contextualize qualitative findings. The findings indicate that preventive policy communication contributed to a decline in prevented non-procedural departures from approximately 54,000 cases in 2022 to 36,000 cases in 2023. Cross-border institutional communication emerged as critical to recalibration implementation but was constrained by data inconsistencies and delayed verification. Additionally, significant discursive gaps persist, as many migrant workers remain distrustful of institutional messages due to fear of enforcement, high perceived costs, and limited digital access. The study demonstrates that migration governance operates as a communicative process shaped by discourse, trust, and institutional interaction. Effective policy communication enhances compliance and protection, while communicative breakdowns reproduce migrant vulnerability. The findings extend policy communication theory by integrating liberal institutionalism and migration governance perspectives.